2020
DOI: 10.1007/s00217-020-03579-9
|View full text |Cite
|
Sign up to set email alerts
|

Gluten hypersensitivities and their impact on the production of gluten-free beer

Abstract: This article consists of a study of the literature and an assessment of available data on the production of gluten-free beer and its constituents. The article shows how the FAO/WHO Codex Alimentarius Commission for Nutrition and Foods for Special Dietary Uses defines celiac disease, gluten-free products, and gluten-free beer. It describes diet-dependent diseases, which require a gluten-free diet, and groups of potential consumers of gluten-free beer. This article describes the use of oats as a raw material for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 85 publications
(148 reference statements)
1
15
0
Order By: Relevance
“…Consumption of beer is toxic to celiac patients and could results into this autoimmune disorder due to the presence of gliadin from wheat gluten, prolamines/hordeins from barley, and secalins from rye [19,56]. Scientific research has shown that the successful long-term management of this autoimmune disorder is strict adherence to GF diets [57][58][59]. Hence, the needs for GF-beer.…”
Section: Gluten-free Beermentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of beer is toxic to celiac patients and could results into this autoimmune disorder due to the presence of gliadin from wheat gluten, prolamines/hordeins from barley, and secalins from rye [19,56]. Scientific research has shown that the successful long-term management of this autoimmune disorder is strict adherence to GF diets [57][58][59]. Hence, the needs for GF-beer.…”
Section: Gluten-free Beermentioning
confidence: 99%
“…Pseudo-cereals malted beer produced from amaranth, buckwheat, and quinoa free of gluten is therefore recommended for celiac patient [56,57,64]. These malted beers contain adequate proteins and relatively high starch with sensory attributes slightly lower compared to beer produced from wheat and barley in respect to their taste, aroma, and mouthfeel when adequately mashed, fermented, and stabilized.…”
Section: Gluten-free Beermentioning
confidence: 99%
“…According to the European Commission guidelines, the gluten-free label can be ascribed to beers made from pseudocereal malts and atypical gluten-free (GF) cereal malts and beers made from typical brewing malts and other malts containing gluten, which have been technologically processed to reduce the gluten level to no more than 20 mg/kg. We can also define very-low-gluten beer as beer made from brewing malts which have undergone special technological processing to reduce the level of gluten to no more than 20-100 mg/kg [105].…”
Section: Raw Materials Influence and Brewing Process Impact On Beer Functionality And Its Compoundsmentioning
confidence: 99%
“…These products derive from enzymatic manipulation of amylolysis and proteolysis of raw materials in the brewing process and are extensively reviewed elsewhere (Cela et al . 2020 ; Gumienna and Gorna 2020 ).…”
Section: Introductionmentioning
confidence: 98%